Contracts in the Sharia Context - Muhammad Latifil Ansori; Murni Aisah; Nur Fitriah; Muhammad Aji Purwanto (Penerbit Hellow Pustaka, 2024)
Akad is a fundamental concept in Islamic law which refers to an agreement or contract that binds two or more parties. This journal aims to provide a comprehensive overview of contracts, starting from the definition to the types based on their nature and scope. By using an approach to specific cases in various contexts of daily life, this research explores how contracts play an important role in completing transactions and negotiating rights and obligations. Methodologically, this research uses a literature study method to analyze various sources of Islamic law and ulama fatwas related to contracts. The results show that contracts are not only limited to economic transactions, but also include social and religious aspects, such as marriage and the Hajj. This research also highlights the importance of fulfilling the conditions for the validity of a contract, including agreement, clarity of content, and legal capacity of the parties.